2021
DOI: 10.3758/s13415-021-00950-5
|View full text |Cite
|
Sign up to set email alerts
|

The reward positivity is sensitive to affective liking

Abstract: The EEG feature known as the Reward Positivity (RewP) is elicited by reward receipt and appears to reflect sensitively and specifically positive prediction errors during reinforcement learning. Yet, the RewP also is modulated by state and trait affect, suggesting that it has a more complex computational role than simple reinforcement surprise. We conducted a series of experiments aimed to investigate underlying affect processing reflected in the RewP during a reinforcement learning task. In the first experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…With a sample size of 141, and α error probability set to 0.05, the smallest effect size we could detect was r = 0.23. Several studies investigating correlations between the RewP and motivation variables have detected associations larger than r = 0.23 (e.g., Angus et al, 2015;Brown et al, 2022;Foti & Hajcak, 2010), suggesting that our sample size would support our analyses. All participants identified as female were at least 18 years old and indicated that they were able to read and write in English.…”
Section: Participantssupporting
confidence: 61%
See 3 more Smart Citations
“…With a sample size of 141, and α error probability set to 0.05, the smallest effect size we could detect was r = 0.23. Several studies investigating correlations between the RewP and motivation variables have detected associations larger than r = 0.23 (e.g., Angus et al, 2015;Brown et al, 2022;Foti & Hajcak, 2010), suggesting that our sample size would support our analyses. All participants identified as female were at least 18 years old and indicated that they were able to read and write in English.…”
Section: Participantssupporting
confidence: 61%
“…RewP magnitude may thus reflect not only subjective liking (Baskin-Sommers & Foti, 2015;Brown et al, 2022), but also wanting (i.e., motivation to attend to and pursue rewarding stimuli; Angus et al, 2015;Huvermann et al, 2021;Threadgill & Gable, 2016). This is congruent with the idea that the RewP is a multidimensional neural marker of reward processing that reflects information about several reward aspects (Brown et al, 2022;Sambrook & Goslin, 2015), including reward outcome probability and magnitude (Heydari & Holroyd, 2016;Holroyd & Coles, 2002;Sambrook & Goslin, 2015), subjective preference (Jia et al, 2013;Peterburs et al, 2019), and approach motivation (Angus et al, 2015;Threadgill & Gable, 2016). Food RewP magnitude was also not significantly associated with time elapsed since participants' last meal, although there was a positive correlation between these variables that did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because we expected to find at least the link of RewP or FN amplitudes and emotional negativity. Several ERP studies in adults appear to indicate that gain-related RewP ERP is modulated by hedonic “liking”, and both state and trait affect(Angus, Kemkes, Schutter, & Harmon-Jones, 2015; Brown, Jackson, & Cavanagh, 2022). However, we do not know such relationship was sex-specific or not, as most of those study did not include sex as an independent variable.…”
Section: Discussionmentioning
confidence: 99%